2021
DOI: 10.3389/fonc.2021.608842
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Hyaluronan-Mediated Motility Receptor Predicts Adverse Outcomes: A Potential Therapeutic Target for Head and Neck Squamous Cell Carcinoma

Abstract: Background: Several studies have shown that the hyaluronan-mediated motility receptor (HMMR) is overexpressed in various cancers and could be a potential prognostic factor. However, further research is still required to determine the prognostic value and potential function of HMMR in head and neck squamous cell carcinoma (HNSCC).Materials and Methods: Transcriptomic expression data were collected from the Cancer Genome Atlas database (TCGA) and Gene Expression Omnibus and the differences in HMMR expression bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Evidence suggests that the HMMR is involved in the occurrence and development of tumors that are dependent on hyaluronan-mediated signaling (Tolg et al, 2003;He et al, 2020). Previous studies indicate that the HMMR is overexpressed in and is a potential prognostic factor in various cancer types, including breast cancer (Liu et al, 2016), head and neck squamous cell carcinoma (Lu et al, 2021), hepatocellular carcinoma (Lu et al, 2020), and other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that the HMMR is involved in the occurrence and development of tumors that are dependent on hyaluronan-mediated signaling (Tolg et al, 2003;He et al, 2020). Previous studies indicate that the HMMR is overexpressed in and is a potential prognostic factor in various cancer types, including breast cancer (Liu et al, 2016), head and neck squamous cell carcinoma (Lu et al, 2021), hepatocellular carcinoma (Lu et al, 2020), and other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they play an important role in various physiological and pathological processes. For example, overexpression of SEC61G and HMMR has been associated with poor prognosis in HNSCC (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a growing number of evidence suggests that HMMR high expression of HMMR is associated with poor prognosis in a variety of tumor types, such as gastric cancer [32], head and neck squamous cell carcinoma [33], lung cancer [14], breast cancer [15]and so on. In our study, Kaplan-Meier Plotter analyses showed that high HMMR expression correlated with worse prognosis in liver, lung, breast, gastric, ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%